A modified DV-Hop algorithm for wireless sensor network localisation. (2018) - Singh, Santar Pal; Sharma, Subhash Chandra
In previous years, wireless sensor networks (WSNs) have gained significant consideration from the industrial and research community. However, WSNs uses are restricted by many obstacles. In several applications, monitored data is of no importance if sensor location is unknown because location is needed to spot the network task. So; it is most significant that nodes address the information with the positions. Hence, localisation is an essential process to determine the nodes' location. The localisation methods broadly classified as: range-based and range-free. Range-based methods use actual distance measures whereas range-free schemes use approximate measures. Hence, the range-free methods are a cost effective alternative to range-based because they don't need any added hardware. However, range-free methods have higher localisation error compared to range-based methods. In this paper, we propose a modified algorithm for localisation based on DV-Hop. The simulation results confirm that proposed algorithm improves the results with respect to localisation error and error variance.